Criminal Law Politics on the Granting of Remissions to Prisoners: Research on Class IIA Prison of Binjai - Nasution, Sudarno Hariadi; Ismaidar, Ismaidar; Sembiring, Tamaulina Br. (PT. Riset Press International, 2025)
Law is a set of rules and principles that regulate social interaction in society, aim to maintain order, and include various institutions and processes for implementing rules as a reality in society. The research was conducted in Binjai City at the Class II A Binjai Correctional Institution (Prison) Office. This research uses an empirical legal approach method, and data obtained in the field are presented descriptively using an empirical normative approach method. This study aims to determine the criminal law policy on granting Remission to inmates at Class II A Binjai Penitentiary and the obstacles faced in granting Remission to inmates at Class II A Binjai Penitentiary. Based on the results of the study, the author obtained that the fulfilment of the right to reduce the sentence (Remission) is based on existing laws and regulations, but to provide the fulfilment of rights (Remission) still requires improvements such as explaining to inmates (prisoners) about the requirements for obtaining Remission, as well as the obstacles faced by inmates (prisoners) in obtaining Remission, one of the factors is from the inmates themselves because the requirements for obtaining Remission are to behave well and be able to create a conducive environment.